Nutrition and sustainability: Harnessing value chains to improve food systems - Allen, Summer L.; de Brauw, Alan; Gelli, Aulo (International Food Policy Research Institute, 2016)
Meeting global goals for nutrition and sustainability will require joint solutions tailored to diverse situations. Value chain analysis provides a promising framework for understanding effective interventions to achieve better outcomes for both health and environment.